Lead isotopic fingerprinting of aerosols to characterize the sources of atmospheric lead in an industrial city of India. (March 2016) - Sen, Indra S.; Bizimis, Michael; Tripathi, Sachchida Nand; Paul, Debajyoti
Abstract: Anthropogenic Pb in the environment is primarily sourced from combustion of fossil fuel and high-temperature industries such as smelters. Identifying the sources and pathways of anthropogenic Pb in the environment is important because Pb toxicity is known to have adverse effects on human health. Pb pollution sources for America, Europe, and China are well documented. However, sources of atmospheric Pb are unknown in India, particularly after leaded gasoline was phased out in 2000. India has a developing economy with a rapidly emerging automobile and high temperature industry, and anthropogenic Pb emission is expected to rise in the next decade. In this study, we report on the Pb-isotope compositions and trace metal ratios of airborne particulates collected in Kanpur, a large city in northern part of India. The study shows that the PM10 aerosols had elevated concentration of Cd, Pb, Zn, As, and Cu in the Kanpur area, however their concentrations are well below the United States Environmental Protection Agency chronic exposure limit. Lead isotopic and trace metal data reveal industrial emission as the plausible source of anthropogenic Pb in the atmosphere in Kanpur. However, Pb isotopic compositions of potential source end-members are required to fully evaluate Pb contamination in India over time. This is the first study that characterizes the isotopic composition of atmospheric Pb in an Indian city after leaded gasoline was phased out by 2000.